Caecal endometriosis causing colo-colic intussusception: a rare cause of bowel obstruction - Thangamani, P.; Kumar, K. Senthil; Sivan, M.; Sushmitha, S. P. (International Surgery Journal, 2022)
Intussusception refers to telescoping of a segment of bowel into adjacent bowel. Only 5% occurs in adults. Causes include neoplasm and inflammatory causes. Caecal endometriosis causing colo colic intussusception is extremely rare condition. A 45-year-old menstruating female presented with complaints of diffuse abdominal pain with vomiting for 10 days. No history of menstrual abnormalities. P/A-mass of 8×5 cm was palpable in right lumbar and umbilical region with mild tenderness. Cect abdomen-colo colic intussusception involving ascending colon and right 2/3rd of transverse colon with no obvious lead point. Patient was taken up for emergency laparotomy and it revealed 1) Intussusception of caecum into ascending colon extending upto hepatic flexure, 2) Multiple black colored nodules over lateral pelvic wall, small bowel, omentum, mesentery, ascending sigmoid colon, 3) Anterior surface of rectum was found to be adherent to posterior surface of uterus and pouch of Douglas inaccessible, 4) Multiple nodes were identified within mesentery. Laparotomy proceeded and gentle manual reduction of intussusceptum was done and growth palpable within caecum, suspecting the growth to be malignant right hemicolectomy with ileocolic end to side anastomosis done. Post operative period uneventful, HPE-endometriosis caecum. Intussusception in adult is rare entity and endometrial mass in caecum acting as lead point has been infrequently reported. Clinical and radiological investigations are of little help in diagnosing endometriosis. Hence, high clinical suspicion is required in patients with previous history of endometriosis.